Construção da memória histórica (2007 - 2019) do ensino médio integrado da escola estadual prof.ª. Esther da Silva Virgolino, Macapá/AP - MOTA, Suelen Carvalho (2024)
Integrated secondary education (EMI) is a stage of basic education that combines secondary education with a technical course. With the advent of Decree No. 5.154/2004, the aim of Integrated Secondary Education is to include human development with vocational training, guaranteeing comprehensive training for apprentices. Thus, the research Construction of the Historical Memory (2007 - 2019) of the Integrated High School of the State School Prof. Esther da Silva Virgolino, Macapá/AP, is related to the line Organization and Memories of Pedagogical Spaces in Professional and Technological Education (EPT), aligned with the proposal of macroproject 4 - on history and memories in the context of EPT, of the Professional Master's Degree course in professional and Technological Education - ProfEPT. In the context of professional education in the state of Amapá, in 2007 the Prof. Esther da Silva Virgolino State School (EEPESV) began offering integrated secondary education to the school community, being the first state school to offer integrated secondary education in computer science and in 2010 it once again innovated, being a pioneer in offering integrated secondary education in Computer Networks and in 2019 it graduated the last classes of this type of education. The study aims to contribute to the construction of the historical memory of the implementation and consolidation of the integrated high school of the technical courses in computer science and computer networks at EEPESV. The research carried out is of a basic nature and for the stage of preparation, organization and analysis of the sources we used, in order to build the memory of professional education at EEPESV, research with a qualitative approach and as for the procedures, bibliographical and documentary research were used. In this work, the theoretical framework was used as a basis for analyzing the results and discussions and as a subsidy for the development of the Esther Informa Blog, which is the Educational Product that was developed from the documentary research with the aim of preserving the material collected and strengthening the memory of the EEPESV EMI, so that it can serve as didactic consultation material and for future research on EPT in the Amapá state education network.